MOTION GRAPHIC PROFIL BAGINDO AZIZCHAN - ZIKRI NOVINDRA, Dr. M. Nasrul Kamal, M.Sn., (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of this design is to present a video learning media of Bagindo Azizchan's profile using motion graphics techniques to Padang city students. Especially students at the age of 8-11 years. And design profiles that are more communicative, interesting and effective.This Bagindo Azizchan profile video design method uses the EleglasssBox method, with the analysis used 5W + 1h (what, who, where, why, and how) so there is a solution to the problem.This design produces audio visual media in the form of motion graphics that can display images and sound as the main media, and is supported by several supporting media including: CD Cover, CD Label, Poster, Notebook, T-shirt, Stickers, X-Banner to support the main media as well as promotion media.Keywords: Profile, Bagindo Azizchan, Motion Grpahic